Chlorinated-based bioceramics incorporated in polycaprolactone membranes - Guimarães, Carolina Curcio Lott; de Souza, Joyce Rodrigues [UNESP]; Campos, Tiago Moreira Bastos; Marques, Thays Oliveira [UNESP]; Kito, Letícia Terumi; Kukulka, Elisa Camargo [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Thim, Gilmar Patrocínio (Wiley, 2024)
The development of bioactive membranes with bone repair properties is great interest in the field of tissue engineering. In this study, we aimed to fabricate and characterize a composite membrane composed of sol–gel synthesized bioceramics and electrospun polycaprolactone (PCL) fibers for bone tissue regeneration applications. The bioceramics were prepared using the sol–gel method with nitrate (N) and chloride (CL) as precursors. PCL and bioceramic solutions were electrospun to obtain ultrafine fiber mats. Raman spectroscopy, x-ray diffraction (XRD), Fourier Transform Infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM) were used to characterize the materials. The results showed that both chlorinated and non-chlorinated bioceramics contained NBOs (non-bridge bonds) and crystallized the α-wollastonite phase, with the chlorinated version doing so at lower temperatures. In vitro tests were performed to evaluate cytotoxicity, cell adhesion, and mineralized matrix formation on the membranes. The composite membranes showed improved cell viability and promoted mineralization nodules formation. This study presents a promising approach for the development of bioactive membranes for bone tissue engineering, with potential applications in bone regeneration therapies.
Keywords: biomaterials; bone; materials engineering; medicine; membranes; sol–gel processes